Accent and prejudice - Tay, Athalie Yan Xin (Nanyang Technological University, 2021)
Past studies have shown that people judge others based on their accent and have revealed that the judgement based on accent can lead to discrimination, which has been proven to have detrimental effects on the person and society. As there have not been present studies working on accent in Singapore, this paper will tackle the question of what the relationship between the demographic and accents in Singapore is. Through participants’ guesses and attitudinal ratings towards speakers with different accents, this study has shown that Singaporeans judge others based on their accent. The findings show that Singaporeans are able to identify a person’s background accurately to a certain extent. The data also indicates that Singaporeans judge people based on what background they think the speaker comes from. Most significantly, for example, they favour speakers who are perceived to have a high education level.